AUTOREGRESSIVE INTEGRATED MOVING AVERAGE FOR COCOA PRODUCTION IN SULAWESI ISLAND 2021-2030 - Tenriawaru, Nixia; Amiruddin, Achmad; Arsyad, Muhammad; Mahyuddin, Mahyuddin; Kharisma, N; Nie, Fengying; Ridwan, Muhammad (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2022)
Agribusiness Cocoa on the island of Sulawesi is very supported by the availability of land plantations to produce production even bigger cocoa with management plant and processing seed good cocoa _ thus producing quality cocoa beans. However Thus, various problems are still just faced in the cultivation of cocoa which resulted in the decline in results production. At the moment this Indonesia's position is ranked third highest, however with problems production faced _ of course just rating this could shift to down, though riches nature and location geographical very support cultivation. Research results use the Autoregressive Integrated Moving Average (ARIMA) method, which shows that the area and cocoa production on Sulawesi Island in 2021-2030 experience fluctuation. Southeast Sulawesi is a province on the island of Sulawesi which has the highest area (445.91 ha) in 2030, however, Central Sulawesi Province occupies a position as the center production major by 2030 with a production of 151.68 tons/ha.